2008
DOI: 10.4103/0028-3886.41993
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene polymorphisms in patients with chronic tension-type headache: A preliminary study

Abstract: It is possible to make reliable comparisons and hypothesis about the homozygous and/or heterozygous presence of S and STin 12/10 alleles which may be in interaction with CTTH. On the other hand, the presence of homozygous L and STin12 alleles may play a protective role against CTTH. It is also possible that heterogeneity among diseases showing the same clinical research will require a lot of effort for individual identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 31 Serum serotonin levels were associated with pain thresholds in patients with chronic pain 32 and were altered in TTH patients. 33 , 34 However, RLS has previously been linked to disturbances of the A11 (dorsal-posterior hypothalamic) dopaminergic system. 35 However, using SPECT imaging, Jhoo et al found that decreased pontine and medullary serotonin transporter availability correlated with the increased severity of RLS, suggesting that RLS may entail brainstem serotonergic tone.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Serum serotonin levels were associated with pain thresholds in patients with chronic pain 32 and were altered in TTH patients. 33 , 34 However, RLS has previously been linked to disturbances of the A11 (dorsal-posterior hypothalamic) dopaminergic system. 35 However, using SPECT imaging, Jhoo et al found that decreased pontine and medullary serotonin transporter availability correlated with the increased severity of RLS, suggesting that RLS may entail brainstem serotonergic tone.…”
Section: Discussionmentioning
confidence: 99%